From Nuremberg to Guantánamo: Medical Ethics Then and Now - Nancy Sherman (Washington University Global Studies Law Review, 2007)
On October 25, 1946, three weeks after the International Military Tribunal at Nuremberg entered its verdicts, the United States established Military Tribunal I for the trial of twenty-three Nazi physicians. The charges, delivered by Brigadier General Telford Taylor on December 9, 1946, form a seminal chapter in the history of medical ethics and, specifically, medical ethics in war. The list of noxious experiments conducted on civilians and prisons of war, and condemned by the Tribunal as war crimes and as crimes against humanity, is by now more or less familiar. That list included: high-altitude experiments; freezing experiments; malaria experiments; sulfanilamide experiments; bone, muscle, and nerve regeneration and bone transplantation experiments; sea water experiments; jaundice and spotted fever experiments; sterilization experiments; experiments with poison and with incendiary bombs. What remains less familiar is the moral mindset of doctors and health care workers who plied their medical skill for morally questionable uses in war. In his 1981 work, The Nazi Doctors, Robert Jay Lifton took up that question, interviewing doctors, many of whom for forty years continued to distance themselves psychologically from their deeds. The questions about moral distancing Lifton raised (though not the questions about criminal experiments) have immediate urgency for us now. Military medical doctors, psychiatrists and psychologists serve in U.S. military prisons in Guantánamo, Abu Ghraib, Kandahar, and, until very recently, in undisclosed CIA operated facilities around the world where medical ethics are again at issue. Moreover, they serve in top positions in the Pentagon, as civilian and military heads of command, who pass orders and regulations to military doctors in the field, and who are in charge of the health of enemy combatants, as well as U.S. soldiers. Because we recently marked the sixtieth anniversary of the judgment at Nuremberg, I want to awaken our collective memory to the ways in which doctors in war, even in a war very different from the one the Nazis fought, can insulate themselves from their moral and professional consciences.
Keywords: Medical ethics; Guantánamo Bay Naval Base (Cuba); Combatants (International law); Military physicians; International